From Digital Interaction to Academic Literacy: Punctuation Use in EFL Academic WhatsApp Group - Vezner Sergey Ivanovich; Isnia Wulan Suci; Octa Pratama Putra (International Journal of English Linguistics, Literature, and Education (IJELLE), 2026)
Digital communication platforms have increasingly become part of academic interaction in higher education, particularly in English as a Foreign Language (EFL) context. WhatsApp Messenger is widely used by lecturers and students for academic communication beyond formal classroom settings. This study explores the use of punctuation in lecturer–student academic WhatsApp Group interactions and examines its relevance to writing awareness and academic literacy development. This research adopted a descriptive qualitative design with a case study approach. The data consisted of written chat messages produced by ten undergraduate EFL students in an academic WhatsApp Group. The analysis focused on identifying the types of punctuation marks most frequently used and examining their functions in relation to meaning clarity, academic tone, and academic politeness in digital academic interaction. The findings indicate that students predominantly used basic punctuation marks, particularly full stops, commas, and question marks, while the use of exclamation marks was limited. These punctuation practices served pragmatic functions that supported clearer meaning-making, appropriate academic tone, and polite lecturer–student communication. The study suggests that academic WhatsApp Group function as transitional spaces for developing early academic writing awareness. Pedagogically, the findings highlight the potential of digital academic interaction as a supportive environment for teaching writing fundamentals in EFL contexts.